Regularized Machine Learning in the Genetic Prediction of Complex Traits - Okser, Sebastian; Pahikkala, Tapio; Airola, Antti; Salakoski, Tapio; Ripatti, Samuli; Aittokallio, Tero (PLoS genetics, 2014)
[...]we discuss some key future advances, open questions and challenges in this developing field, when moving toward low-frequency variants and cross-phenotype interactions. Multivariate modeling approaches have already been shown to provide improved insights into genetic mechanisms and the interaction networks behind many complex traits, including atherosclerosis, coronary heart disease, and lipid levels, which would have gone undetected using the standard univariate modeling [2], [19]-[22].